Deterministic chaos theory and forecasting in Social Sciences. Contribution to the discussion - Donaj, Łukasz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
Forecasting social phenomena may be hampered in many ways. This is because in nature of these phenomena lies strong and multilateral connection with other social phenomena; but not only – also physical and biological (natural) ones. The content of this publication constitutes presentation of chosen problems of forecasting in social sciences. The attention in the article was focused among others on deterministic chaos theory, on the attempt of its implementation to phenomena from the scope (or from borderline) of social sciences: economy, logistics, science about safety etc. Moreover, one of the threads of ponderation was the attempt to consider whether it’s possible to create so-called final theory. The aim of the publication is to signalize possibilities of taking advantage of seemingly exotic for “political scientists” methodology of modeling and explaining phenomena, having its source in exact sciences (in chaos theory) to study social phenomena and processes.

Prognozowanie zjawisk społecznych bywa pod wieloma względami utrudnione. Wynika to stąd, że w naturze tych zjawisk tkwi silne i wielostronne powiązanie z innymi zjawiskami społecznymi; ale nie tylko – także fizycznymi czy biologicznymi (przyrodniczymi). Treścią publikacji jest przedstawienie wybranych problemów prognozowania w naukach społecznych. W artykule skoncentrowano się m.in. na teorii chaosu zdeterminizowanego, na próbie jej implementacji do zjawisk z zakresu (lub z pogranicza) nauk społecznych: ekonomii, logistyki, nauki o bezpieczeństwie etc. Jednym z wątków rozważań była ponadto próba rozważenia, czy możliwe jest stworzenie tzw. teorii finalnej. Celem publikacji jest zatem zasygnalizowanie możliwości wykorzystania tak zdawałoby się egzotycznej dla „politologów” metodologii modelowania i wyjaśniania zjawisk, mającej źródło w naukach ścisłych (w teorii chaosu), do badania zjawisk i procesów społecznych.
Teoria chaosu zdeterminowanego a prognozowanie w naukach społecznych. Przyczynek do dyskusji
Keywords: forecasting; social sciences; deterministic chaos theory; catastrophe theory; bifurcation; prognozowanie; nauki społeczne; teoria chaosu zdeterminizowanego; teoria katastrof; bifurkacja